2009
DOI: 10.3892/or_00000311
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between adenosine receptor (A2A isoform) and ERα mediates ethanol action in MCF-7 breast cancer cells

Abstract: Abstract. Alcohol consumption increases the risk of breast cancer but the underlying mechanisms are not well understood. We have shown previously that ethanol activates ER signalling pathway in a cAMP/PKA-mediated ligandindependent manner. Since the activation of A 2A adenosine receptor (A 2A AR) by ethanol has been reported in other cell types, here we tested if cross-talk between this Gs-coupled receptor and ER· could be involved in ethanol effects in breast cancer cells. Our study shows that A 2A AR is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Studies have also shown an anti-tumor action of A 2A AR in A375 melanoma (Merighi et al, 2002) and human colon cancer cells (Yasuda et al, 2009), the latter mediated by activation of caspases. In contrast, the A 2A AR promotes growth of breast cancer MCF-7 breast cancer cells (Etique et al, 2009) and increases angiogenesis by inducing VEGF expression (Montesinos et al, 2002). These studies suggest that A 2A AR antagonists could be useful in cancer by blocking angiogenesis.…”
Section: Adenosine Receptors In Cancermentioning
confidence: 96%
“…Studies have also shown an anti-tumor action of A 2A AR in A375 melanoma (Merighi et al, 2002) and human colon cancer cells (Yasuda et al, 2009), the latter mediated by activation of caspases. In contrast, the A 2A AR promotes growth of breast cancer MCF-7 breast cancer cells (Etique et al, 2009) and increases angiogenesis by inducing VEGF expression (Montesinos et al, 2002). These studies suggest that A 2A AR antagonists could be useful in cancer by blocking angiogenesis.…”
Section: Adenosine Receptors In Cancermentioning
confidence: 96%
“…A2AR is highly expressed in certain tumors, such as head and neck squamous cell carcinoma and breast cancer. This high expression is significantly associated with increased tumor volume, advanced pathological grade, and diminished overall survival 97–99 . The previous studies have shown that blocking A2AR in mice can enhance the immune response against tumors and inhibit tumor growth and metastasis 100 .…”
Section: Purines and Purinergic Receptors In Tumorsmentioning
confidence: 99%
“…This high expression is significantly associated with increased tumor volume, advanced pathological grade, and diminished overall survival. 97 , 98 , 99 The previous studies have shown that blocking A2AR in mice can enhance the immune response against tumors and inhibit tumor growth and metastasis. 100 In the investigation of adenosine receptors’ role in cancer cells, A2BR and A2BR have emerged as two extensively studied receptors (Tables 2 and 3 ).…”
Section: Purines and Purinergic Receptors In Tumorsmentioning
confidence: 99%
“…The activation of ADORA on tumor cells regulates cell proliferation, apoptosis, cytoprotection and migration [199,200]. In particular, the adenosine A2A receptor (ADORA2a) has been found to be overexpressed in HNSCC [201,202] and in several melanoma and breast cancer cell lines [203][204][205]. The ADORA2a downstream pathway inhibits JAK/STAT signaling, either by preventing phosphorylation or inducing the proteasomal degradation of STAT proteins [206].…”
Section: Cd38 and Adenosine Receptor Activationmentioning
confidence: 99%